1H, 13C and 15N resonance assignments for the oxidized and reduced states of the N-terminal domain of DsbD from Escherichia coli. - Mavridou, D; Stelzl, L; Ferguson, S; Redfield, C (Springer Netherlands, 2012)
Viability and pathogenicity of Gram-negative bacteria is linked to the cytochrome c maturation and the oxidative protein folding systems in the periplasm. The transmembrane reductant conductor DsbD is a unique protein which provides the necessary reducing power to both systems through thiol-disulfide exchange reactions in a complex network of protein-protein interactions. The N-terminal domain of DsbD (nDsbD) is the delivery point of the reducing power originating from cytoplasmic thioredoxin to a variety of periplasmic partners. Here we report (1)H, (13)C and (15)N assignments for resonances of nDsbD in its oxidized and reduced states. These assignments provide the starting point for detailed investigations of the interactions of nDsbD with its protein partners.